In the depths of the Amazon rainforest: a new troglobitic species of Circoniscus (Isopoda: Scleropactidae) from Brazil - Júlia Barbosa Galo; Giovanna Monticelli Cardoso; Rodrigo Lopes Ferreira (Nauplius)
ABSTRACT Scleropactidae are one of the most abundant families of Oniscidea, comprising 28 genera. Within this family, the genus Circoniscus includes 13 species, of which four are troglobitic. We herein describe the fifth troglobitic species of the genus, which represents the first species described from the largest limestone cave of the Brazilian Amazon, Paraíso cave. Circoniscus paradisus sp. nov. differs from the troglobitic species by the presence of schisma on pereonite 1 in all specimens, antennula with 2+9 aesthetascs, distal margin of male pleopod 1 exopod elongated, and pereonites epimera inner face with continuous ridge. Additionally, we provide ecological notes, habitat description, and the conservation status for the newly described species.